Some Correspondence on Methodology between Milton Friedman and Edwin B. Wilson; November-December 1946 - Stigler, Stephen M. (Journal of Economic Literature, 1994)
casual empiricism, invalid use of inverse probability, introduction of factors external to the theoretical system, and the use of only some of the implications of a formal model that has others that are unrealistic. . . . The basic sources of the defects in Lange's theoretical analysis are the emphasis on formal structure, the attempt to generalize without first specifying in detail the facts to be generalized, and the failure to recognize that the ultimate test of the validity of a theory is not conformity to the canons of formal logic but the ability to deduce facts that have not yet been observed, that are capable of being contradicted by observation, that subsequent observation does not contradict. In consequence, these defects are found in much economic theorizing that is not taxonomic in character. They are, however, especially likely to arise when the taxonomic approach is adopted, as their presence in the writings of saable and careful a theorist as Lange testifies. (Friedman 1946, p. 631) Shortly after the publication of the piece on Lange, Friedman received a probing letter from Edwin Bidwell Wilson. That letter, Friedman's reply, and a second letter of Wilson's are reprinted below. E. B. Wilson (1879-1964) was a scientific generalist of a type that has always been uncommon, and is becoming unknown. Wilson studied under the mathematical physicist J. Willard Gibbs, and his publication of Gibbs' notes on vector analysis and a text of his own on advanced calculus had a great impact upon education in advanced mathematics in the early part of this century. Wilson held faculty positions in mathematics at Yale and mathematics and physics at M.I.T. before he moved in 1922 from being the Chairman of Physics at M.I.T. to Harvard to be Professor of Vital Statistics in the Harvard School of Public Health, a position he held until his retirement. In 1914 he was appointed Managing Editor of the Proceedings of the National Academy of Sciences, a post he held for fifty years, until his death. In 1929 he served as President of the American Statistical